Functionalized magnetic nanoparticle-reduced graphene oxide nanocomposite for enzymatic biofuel cell applications. (25th October 2019) - Shakeel, Nimra; Ahamed, Mohd Imran; Ahmed, Anees; Inamuddin; Rahman, Mohammed Muzibur; Asiri, Abdullah M.
Abstract: Enzymatic biofuel cells (EBFCs) produce electrical energy from green and renewable fuels, by utilizing redox enzyme. However, the main issue of low power output and stability of the electrode still prevails in this field. Extensive research is going on to overcome this problem by improving the electrical communication between the enzyme and the current collector. In the light of this, a new electrode design based on reduced graphene oxide (rGO) and functionalized magnetic nanoparticles (f-Fe3 O4 NPs) in polyaniline matrix has been proposed and employed for the purpose of the EBFCs application, in order to achieve efficient electron shuttling between enzyme glucose oxidase (GOx) and the electrode surface. The as-prepared rGO/PANI/f-Fe3 O4 nanocomposite was examined by analytical techniques viz, Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), transmission electron microscopy (TEM) and the electrochemical behaviour of the rGO/PANI/f-Fe3 O4 nanocomposite and rGO/PANI/f-Fe3 O4 /Frt/GOx bioanode was determined by cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS), and linear sweep voltammetry (LSV). The bioanode attained a maximum current density of 32.9 mA cm −2 at the optimum glucose concentration of 50 mM. Highlights: Surface modification of rGO coated polyaniline with amine functionalized magnetic nanoparticles. Hydrothermal synthesis of functionalized magnetic nanoparticles. Effective glucose oxidase wiring to the nanocomposite modified electrode. Bioanode performances as function of the glucose concentration with an optimum concentration of 50 mM.